Comparative analysis of the mechanisms of sulfur anion oxidation and reduction by dsr operon to maintain environmental sulfur balance. (December 2015) - Ghosh, Semanti; Bagchi, Angshuman
Graphical abstract: Abstract: Sulfur metabolism is one of the oldest known redox geochemical cycles in our atmosphere. These redox processes utilize different sulfur anions and the reactions are performed by the gene products of dsr operon from phylogenetically diverse sets of microorganisms. The operon is involved in the maintenance of environmental sulfur balance. Interestingly, the dsr operon is found to be present in both sulfur anion oxidizing and reducing microorganisms and in both types of organisms DsrAB protein complex plays a vital role. Though there are various reports regarding the genetics of dsr operon there are practically no reports dealing with the structural aspects of sulfur metabolism by dsr operon. In our present study, we tried to compare the mechanisms of sulfur anion oxidation and reduction by Allochromatium vinosum and Desulfovibrio vulgaris respectively through DsrAB protein complex. We analyzed the modes of bindings of sulfur anions to the DsrAB protein complex and observed that for sulfur anion oxidizers, sulfide and thiosulfate are the best substrates whereas for reducers sulfate and sulfite have the best binding abilities. We analyzed the binding interaction pattern of the DsrA and DsrB proteins while forming the DsrAB protein complexes in Desulfovibrio vulgaris and Allochromatium vinosum . To our knowledge this is the first report that analyzes the differences in binding patterns of sulfur substrates with DsrAB protein from these two microorganisms. This study would therefore be essential to predict the biochemical mechanism of sulfur anion oxidation and reduction by these two microorganisms i.e., Desulfovibrio vulgaris (sulfur anion reducer) and Allochromatium vinosum (sulfur anion oxidizer). Our observations also highlight the mechanism of sulfur geochemical cycle which has important implications in future study of sulfur metabolism as it has a huge application in waste remediation and production of industrial bio-products viz. vitamins, bio-polyesters and bio-hydrogen.